Local public servants and employees in the Republic of Croatia: legal position and obligations - Lozina, Duško (Lex localis, 2008)
The topic of this paper is an analysis of the legal position of local public servants and employees in the Republic of Croatia as well as of their rights and obligations in the light of the enactment of the Public Servants and Employees in local and regional self-government Act. In this sense, the concept and characteristics of the status of the administrative public servant from the aspect of administrative theory and practice are analysed, a short comparative overview of different official systems in Europe is given, and the position of local public servants and employees in Croatia in the light of positive legal regulations is analysed. In the conclusion, an assessment of the existing officials system which is related to local public servants and employees in Croatia is given in the context of the stated modern systems of public administration. Also assessed is whether the enacted legal regulations will have a positive effect on the implementation of personnel policy, greater motivation and the work of local public servants and employees thereby finally resulting in a better and more quality functioning of local self-government.
Keywords: Hrvaška; javna uprava; javni uslužbenci; upravno pravo